THE EXPRESSION OF LOVE IN THE POEM NÄHE DES GELIEBTEN BY JOHANN WOLFGANG VON GOETHE (A STRUCTURAL-SEMIOTIC STUDY) - Patricia Tampanguma; Sjuul J. Lendo; Prilimercy E. Kojongian (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2022)
This research aims to describe and analyze the inner structure, physical structure as well as the meaning of the expression of love contained in the poem Nähe Des Geliebten by Johann Wolfgang Von Goethe. The method used in this research is a qualitative descriptive method with library research as a data collection technique and a structural-semiotic approach as a data analysis technique. In the structural approach there are the essence of poetry and poetic methods, while in semiotics there are heuristic readings, hermeneutic readings, and three aspects of signs according to Pierce namely Icons, Indexes and Symbols. The results of this study conclude that the interesting thing that can be expressed from the poem